2014
DOI: 10.1016/j.amjmed.2013.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Emphysema Subtypes on Computed Tomography: The MESA COPD Study

Abstract: Background Pulmonary emphysema is divided into three major subtypes at autopsy: centrilobular, paraseptal and panlobular emphysema. These subtypes can be defined by visual assessment on computed tomography (CT); however, clinical characteristics of emphysema subtypes on CT are not well-defined. We developed a reliable approach to visual assessment of emphysema subtypes on CT and examined if emphysema subtypes have distinct characteristics. Methods The Multi-Ethnic Study of Atherosclerosis COPD Study recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
186
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(213 citation statements)
references
References 56 publications
21
186
4
2
Order By: Relevance
“…The relative contribution of these two processes varies across individuals and emphysematous destruction is further categorized based on its morphology: centrilobular emphysema (CLE), panlobular emphysema (PLE), and paraseptal emphysema (1)(2)(3). These pathologic features underlie various clinical and radiographic manifestations in COPD and, in particular, CLE and PLE have been recognized as distinct pathologic phenotypes (3)(4)(5)(6). Histologic comparisons have shown that emphysematous destruction is more heterogeneous and small airway disease is more severe in CLE than in PLE (4,5,7).…”
Section: Measurements and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative contribution of these two processes varies across individuals and emphysematous destruction is further categorized based on its morphology: centrilobular emphysema (CLE), panlobular emphysema (PLE), and paraseptal emphysema (1)(2)(3). These pathologic features underlie various clinical and radiographic manifestations in COPD and, in particular, CLE and PLE have been recognized as distinct pathologic phenotypes (3)(4)(5)(6). Histologic comparisons have shown that emphysematous destruction is more heterogeneous and small airway disease is more severe in CLE than in PLE (4,5,7).…”
Section: Measurements and Main Resultsmentioning
confidence: 99%
“…This imaging technique has been widely used to describe and quantify all of the classic pathologic phenotypes of emphysematous destruction in COPD (3,6,9) and to measure the changes in lumen and wall of airways 2 mm in diameter and larger (10)(11)(12). Although new-generation CT scanners have the potential for greater resolution without an increase in radiation dose (13,14) and may enable measurements of airways less than 2 mm in diameter, it is not currently possible to resolve the small conducting airways down to the level of the terminal bronchioles.…”
Section: Measurements and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CT imaging can visualise these different sub-types. One study using a visual scoring system found that centrilobular emphysema was the most common sub-type but over half of patients with emphysema had multiple sub-types [53]. An automated method, called local histogram-based emphysema patterns involves dividing the lung into small cubes and analysing the sub-type of emphysema present in each cube.…”
Section: Emphysemamentioning
confidence: 99%
“…Це відповідає літературним даним про те, що най-більш частим варіантом емфіземи у хворих на ХОЗЛ є саме центрилобулярне ураження з переважно верхньо-дольовою локалізацією [23].…”
Section: український пульмонологічний журнал 2018 №unclassified